Growth of farm animals - Lawrence, T. L. J. (CABI, 2002)
This book contains 16 chapters. Topics covered are: general aspects of growth; cells; tissues: basic structure and growth; tissues: growth and structure relative to product value for human consumption; mammary gland growth and product yield; hormonal influences on growth; genetic influences on growth; immune system and growth; gametes, fertilization and embryonic growth; prenatal and postnatal growth; efficiency and growth; compensatory growth; growth and puberty in breeding animals; measuring growth; growth promoters, performance enhancers, feed additives and alternative approaches; the future.